Distribution, population structure and life cycle of the Mediterranean endemic Laminaria rodriguezii (Laminariales, Phaeophyceae) - THIERRY , THIBAUT; BLANFUNÉ, AURÉLIE; THOUROUDE, BASTIEN; REYNES, LAURIC; BALLESTA, LAURENT; HOLON, FLORIAN; DETER, JULIE; BOUDOURESQUE, CHARLES-FRANÇOIS; VALENTIN, KLAUS-ULRICH; WAGNER, ANDREAS; BARTSCH, INKA (Mediterranean Marine Science, 2025)
Laminaria rodriguezii is a rare deep-water kelp species, endemic to the Mediterranean Sea, known in only 19 locations, 5 along the Eastern Provence and 14 in Corsica (French coasts). Populations are found at depths ranging from 48 to 100 m; the oldest record dates back to 1954. This study aims to better understand its distribution, biology, and ecology by analyzing recent data from in situ observations and sampling. In July 2019, a population at Magaud Bank (France) was studied at 75 m depth. A total of 154 individuals were collected in quadrats, showing an average density of 15.7 ± 2.2 individuals per m2 (mean ± SE). The population consists mostly of small blades, with 80% measuring < 40 cm in total length. The blades generally have a single lobe, corresponding to the year 2019, but sometimes 2 to 3 superimposed lobes, corresponding to the growth of the years 2018 and 2019 respectively. Lobe density ranged from 6 to 84 lobes per m2, and the dry mass (DM) varied from 24 to 1160 g DM m-2. A small percentage (17%) of individuals bore small, mostly released sori on the 2018 lobes, and some blades showed signs of herbivory (7%) and breakage (44%). In culture, we verified the typical heteromorphous haplodiplontic life cycle of Laminaria species, with microscopic dimorphic male and female gametophytes. In addition, we showed that vegetative sporophyte reproduction is possible from haptera and stolons. Except for 7 locations (in Corsica) that were not examined, all the French historical populations are still present, and we propose a Least Concern IUCN status for the species. Considering their resistance to the few disturbances likely to threaten the species (mainly fishing using tremail nets), proposals for conservation measures along the French coast are discussed.